The Cambridge handbook of Twin Peaks financial regulation / edited by Andrew Godwin, Andrew Schmulow. - Godwin, Andrew; Schmulow, Andrew, 1970- (Cambridge University Press, 2021)
First proposed in 1994, the Twin Peaks model of financial system regulation employs two specialist peak regulators: one charged with the maintenance of financial system stability, and the other with market conduct and consumer protection. This volume, with contributions from over thirty scholars and senior regulators, provides an in-depth analysis of the similarities and differences in the Twin Peaks regimes that have been adopted around the world. Chapters examine the strengths and weaknesses of the model, provide lessons from Australia (the first to adopt the model), and offer a comparative look at the potential suitability of the model in leading non-Twin Peaks jurisdictions. A key resource for central bankers, public policy analysts, lawyers, economists, politicians, academics and students, this work provides readers with a comprehensive understanding of the Twin Peaks model, and a roadmap for countries considering its adoption.